Evaluation of a Combination of Qualitative and Quantitative Features in Chronic Glomerulonephritis in Children with Atopic Dermatitis - Каримова У. Н. (Scholars Digest Publishing, 2023)
In recent decades, there has been a steady increase in nephropathies among the child population. Among many kidney diseases, glomerulonephritis (GN) has a special place due to the severity of its course, the complexity of treatment, the ambiguity of the prognosis and the steady progression towards chronic renal failure (CKD), which leads to disability of patients. CKD in children as a cause of disability occurs with a frequency of 5:100,000 in the pediatric population. According to foreign studies, the risk of developing end-stage CKD by the age of 20 in children with chronic glomerulonephritis (CGN) is 68.0%.